EP122/#80 Uptake in sentinel lymph node biopsy for endometrial cancer with T3 classification. (4th December 2022) - Khetan, Varun; Vallejo, Andrew; Violette, Caroline; Tavakoli, Amin; Klar, Maximilian; Roman, Lynda; Wright, Jason; Matsuo, Koji
Abstract : Objectives: Current practice guidelines for endometrial cancer specify sentinel lymph node biopsy for intra-uterine disease, now with increasing utilization in T2 extra-uterine disease. The objective of this study was to examine trends and outcomes related to SLN biopsy for endometrial cancer with T3 classification, another extra-uterine disease. Methods: A population-based retrospective cohort study was conducted to examine 7, 004 women with T3 endometrial cancer who underwent primary surgery between 2010–2018, identified in the National Cancer Institute's Surveillance, Epidemiology, and End Results Program. Trends and characteristics related to SLN biopsy were assessed by multinomial regression analysis, and inverse probability of treatment weighting propensity score was used to assess overall survival related to SLN biopsy. Results: Nodal evaluation type included lymphadenectomy (n=5, 276, 75.3%), SLN biopsy (n=287, 4.1%), and none (n=1, 441, 20.6%). The utilization of SLN biopsy increased from 0.4% to 12.9% between 2010–2018 (P<0.001) that this association remained independent in multivariable analysis (adjusted-odds ratio compared to 2010–2012, 2.63 for 2013–2015 and 10.1 for 2016–2018). When compared to the lymphadenectomy group, the SLN biopsy group was less likely to have T3b disease (adjusted-odds ratio 0.69, 95% confidence interval 0.51–0.94) but had similar postoperative chemotherapy and radiotherapy (both, P>0.05). In a weighted model, the 3-year overall survival rate was 66.3% for the SLN biopsy group and 64.7% for the lymphadenectomy group (hazard ratio 0.85, 95% confidence interval 0.69–1.05). Similar association was observed in subcohorts for young, old, endometrioid, non-endometrioid, T3a, T3b, and N0 cases. Conclusions: Utilization of SLN biopsy in T3 endometrial cancer is increasing in the United States.